ANALYSING THE IMPLEMENTATION AND THE EFFECT OF PARTNERSHIP AMONG SCHOOL, FAMILY, AND COMMUNITY TOWARDS THE QUALITY OF EDUCATION IN SD NEGERI 02 KARANGSARI KEBUMEN - Suhartono Suhartono; Siti Fatimah; Setyana Widyastuti (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2018)
This study aims to analyze the implementation of partnerships among school, families, and communities, as the educational centers, in primary schools as well as the influence of partnerships towards the quality of education. The subject of this research is SD Negeri 02 Karangsari Kebumen which has implemented a partnership among three educational centers. This study is a survey research. A questionnaire was utilized as an instrument of research. The quantitative descriptive was a technique used in the data analysis process. The analysis results show that: (1) the implementation of partnership among educational centers in SD Negeri 02 Karangsari Kebumen achieved a "Good" category and the percentage of implementation was 78.45%; (2) there were several recommendations for enhancing the partnerships in SD Negeri 02 Karangsari Kebumen: strengthening parenting programs, strengthening the culture of literacy, providing access and facilities for children with special needs, profession seminars, and the cultivation of the souls of nationalism in learning; (3) the partnership of educational centers has an effect towards the quality of education in SD Negeri 02 Karangsari Kebumen. Keywords: school-family-community partnerships, quality of education